2010
DOI: 10.1017/s0007114510002321
|View full text |Cite
|
Sign up to set email alerts
|

Acute supplementation with keto analogues and amino acids in rats during resistance exercise

Abstract: During exercise, ammonia levels are related to the appearance of both central and peripheral fatigue. Therefore, controlling the increase in ammonia levels is an important strategy in ameliorating the metabolic response to exercise and in improving athletic performance. Free amino acids can be used as substrates for ATP synthesis that produces ammonia as a side product. Keto analogues act in an opposite way, being used to synthesise amino acids whilst decreasing free ammonia in the blood. Adult male rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…However, two relevant studies have been reported [8,22]. In a study of adult rats, De Almeida et al have shown that exercise increased ammonia levels twofold with respect to the control and significantly increased blood urea levels (17%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two relevant studies have been reported [8,22]. In a study of adult rats, De Almeida et al have shown that exercise increased ammonia levels twofold with respect to the control and significantly increased blood urea levels (17%).…”
Section: Discussionmentioning
confidence: 99%
“…BCAA supplementation was reported to increase endurance capacity in trained individuals [18,19], but this result was not supported by other studies [20,21]. In addition, the combination of the keto analog and amino acid supplementation was reported to attenuate the increase in blood ammonia concentration after an exercise bout [8,22]. However, studies of the effects of α-keto acid supplementation (KAS) seem to be principally limited to pathological conditions such as renal or hepatic disorders, and the effects of KAS alone on physical exercise in healthy subjects remain unknown.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some of these changes in metabolism can be assessed using blood as a biological matrix. For more than one decade, our group has dedicated research efforts towards understanding changes in metabolism using exercise as an induced-stress metabolic model [3,5,6,7,8,9,10,11,12,13,14,15,16]. The Sportomics approach targets metabolic and signaling molecule evaluations during either mimicked or real conditions faced in sports situations; it combines “-omics” technique with classic clinical laboratory analyses in order to understand sport-induced modifications [16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ammonia accumulation may be avoided through a detoxification system. Humans convert ammonia to urea mainly in hepatocytes, and different cells can decrease ammonemia by synthesizing amino acids as a mechanism for further excretion of urea [9,11,37]. Therefore, an increase in urea levels reflects both AMP and amino acid deamination.…”
Section: Introductionmentioning
confidence: 99%